2021
DOI: 10.3390/nu14010103
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic-Associated Fatty Liver Disease (MAFLD), Diabetes, and Cardiovascular Disease: Associations with Fructose Metabolism and Gut Microbiota

Abstract: Non-alcoholic fatty liver disease (NAFLD) is an increasingly common condition associated with type 2 diabetes (T2DM) and cardiovascular disease (CVD). Since systemic metabolic dysfunction underlies NAFLD, the current nomenclature has been revised, and the term metabolic-associated fatty liver disease (MAFLD) has been proposed. The new definition emphasizes the bidirectional relationships and increases awareness in looking for fatty liver disease among patients with T2DM and CVD or its risk factors, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 164 publications
1
31
0
3
Order By: Relevance
“…In turn, hepatic steatosis is characterized by atherogenic dyslipidemia: high levels of TG and LDL, and low levels of HDL, increasing obesity and cardiovascular disease risk [9,10]. Since multiple metabolic disorders underlie NAFLD, the term has been introduced to denote it-metabolic-associated fatty liver disease (NAFLD) [11]. The new term stresses the bidirectional relationships and increases awareness in looking for fatty liver disease among patients with MS/DM2T and CVD or separate cardiovascular risk factors, as well as revealing these comorbidities among patients with NAFLD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, hepatic steatosis is characterized by atherogenic dyslipidemia: high levels of TG and LDL, and low levels of HDL, increasing obesity and cardiovascular disease risk [9,10]. Since multiple metabolic disorders underlie NAFLD, the term has been introduced to denote it-metabolic-associated fatty liver disease (NAFLD) [11]. The new term stresses the bidirectional relationships and increases awareness in looking for fatty liver disease among patients with MS/DM2T and CVD or separate cardiovascular risk factors, as well as revealing these comorbidities among patients with NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Today, the first-line MS and NAFLD therapy are lifestyle changes-body weight reduction via a healthy diet and/or individualized physical activity regimens [6][7][8]11]. However, low-intensity exercise training, which triggers no significant changes in immunological and physiological reactions and does not lead to the desired effects, remains the only available option for a large number of patients with cardiometabolic pathology accompanied by musculoskeletal disorders [13].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic lipid accumulation and steatosis, as the initiating stage of the NAFLD disease course, are important for controlling disease progression. According to recent studies, IR plays a central role in hepatic steatosis, and calls to rename NAFLD as metabolic-associated fatty liver disease as a way to emphasize the close association between obesity, type 2 diabetes mellitus (T2DM), and the MetS, have intensified in the last two years [ 18 ]. However, a cross-sectional study based on US adults showed a prevalence of 37.1% and 39.1% for NAFLD and MAFLD, respectively.…”
Section: Nafldmentioning
confidence: 99%
“…How could fructose alter blood pressure and affect circulation? During the last years, possible mechanisms regarding the interaction of fructose and blood pressure have repeatedly been reviewed (for an overview see [50,109,110]). Therefore, in the present review, we will only briefly highlight some of the possible mechanisms involved in the fructose-induced elevation of blood pressure found in some human studies.…”
Section: Effect Of Fructose On Blood Pressure and The Development Of ...mentioning
confidence: 99%